The Effect of Payment Methods on Purchase Decisions Through Purchase Intentions as an Intervening Variable on Kopi Kenangan Merak in Samarinda - Maulana, Valdi Haris; Istimaroh, Istimaroh (Research in Management of Technology and Business, 2024)
Along with economic growth in the current era of globalization, people are increasingly paying attention to ease of payment. In Indonesia, there is an increase in payment methods that make transactions easier. This study aims to determine the effect of Payment Methods on Purchase Decisions through Purchase Intentions as an intervening variable at Kopi Kenangan Merak in Samarinda. The population in this study are consumers who have purchased products at Kopi Kenangan and have purchased at Kopi Kenangan. This study uses descriptive quantitative type. The sample used in this study was 213 respondents who were taken by non-probability sampling method using accidental sampling. The data collection technique was carried out using a questionnaire in the form of a Google Form link. The data processing method of this research is using IBM SPSS software version 26 and SmartPLS software version 4.0.2. The results in this study indicate that payment methods have a positive and significant effect on purchase decisions, payment methods have a positive and significant impact on purchase intentions, purchase intentions have a positive and significant effect on purchase decisions, payment methods have a positive and significant impact on purchase decisions through purchase intentions as an intervening variable.